PENGARUH LINGKUNGAN BELAJAR DAN VARIASI MENGAJAR GURU TERHADAP MINAT BELAJAR PADA MATA PELAJARAN EKONOMI SISWA KELAS XI IPS DI SMA NEGERI 1 KOTO GASIB - Zulfaini Zulfaini; Gimin Gimin; Suarman Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to know the influence of learning environment and variety of teaching teachers against interest studied economics students in SMA Negeri 1 Koto Gasib. The population in this research is the whole grade XI IPS in SMA Negeri 1 Koto Gasib as many as 57 students and on research using a sample census technique where all the population be used as samples. Data were collected using a questionnaire about the learning environment, the teacher and the teaching variations of interest study distributed to respondents. Data on analisisis using multiple linear regression test. In descriptive, at umunya students have a learning environment on the category either (75.4%), teachers teach variations on categories varies (71.9%), and interest in learning on the category are (77.2%). Through multiple linear regression shows analisisis learning environment and variety of teaching teachers has a positive influence and interest significantly to student learning with a donation of 14.6% and the regression equation Y = 32,146 + 0, 204X1 + 219X2. Based on the results of the research, then the author will provide suggestions that are expected to benefit, that is, parents can help provide and create a conducive learning environment for his son to learn well, the teacher should carry out varied learning in order to enhance students ' interest in learning, students to continue to improve the learning interest and make use of existing learning environments at home and focus on learning in schools, and for the researchers next study is expected to be a reference and develop research by adding variable other than the learning environment and variety of teaching teachers as social economic status of parents, the results of the study, and other variables affect learning interest of students.Key Words: Learning environment, variations of teacher teaching, learning interest.